Platelets in Myocardial Ischemia/Reperfusion Injury - Schanze, Nancy; Hamad, Muataz Ali; Nührenberg, Thomas Georg; Bode, Christoph; Duerschmied, Daniel (Hämostaseologie, 2022)
Coronary artery disease, including myocardial infarction (MI), remains a leading cause of global mortality. Rapid reperfusion therapy is key to the improvement of patient outcome but contributes substantially to the final cardiac damage. This phenomenon is called “ischemia/reperfusion injury (IRI).” The underlying mechanisms of IRI are complex and not fully understood. Contributing cellular and molecular mechanisms involve the formation of microthrombi, alterations in ion concentrations, pH shifts, dysregulation of osmolality, and, importantly, inflammation. Beyond their known action as drivers of the development of coronary plaques leading to MI, platelets have been identified as important mediators in myocardial IRI. Circulating platelets are activated by the IRI-provoked damages in the vascular endothelium. This leads to platelet adherence to the reperfused endothelium, aggregation, and the formation of microthrombi. Furthermore, activated platelets release vasoconstrictive substances, act via surface molecules, and enhance leukocyte infiltration into post-IR tissue, that is, via platelet–leukocyte complexes. A better understanding of platelet contributions to myocardial IRI, including their interaction with other lesion-associated cells, is necessary to develop effective treatment strategies to prevent IRI and further improve the condition of the reperfused myocardium. In this review, we briefly summarize platelet properties that modulate IRI. We also describe the beneficial impacts of antiplatelet agents as well as their mechanisms of action in IRI beyond classic effects.
Keywords: myocardial infarction; ischemia reperfusion injury; platelets; reperfusion; ischemia